2018
DOI: 10.3390/molecules23030695
|View full text |Cite
|
Sign up to set email alerts
|

Gallic Acid Content and an Antioxidant Mechanism Are Responsible for the Antiproliferative Activity of ‘Ataulfo’ Mango Peel on LS180 Cells

Abstract: Mango “Ataulfo” peel is a rich source of polyphenols (PP), with antioxidant and anti-cancer properties; however, it is unknown whether such antiproliferative activity is related to PP’s antioxidant activity. The content (HPLC-DAD), antioxidant (DPPH, FRAP, ORAC), and antiproliferative activities (MTT) of free (FP) and chemically-released PP from mango ‘Ataulfo’ peel after alkaline (AKP) and acid (AP) hydrolysis, were evaluated. AKP fraction was higher (µg/g DW) in gallic acid (GA; 23,816 ± 284) than AP (5610 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(81 citation statements)
references
References 67 publications
5
76
0
Order By: Relevance
“…Recently, Velderrain‐Rodríguez et al . () demonstrated that 45.7 μg mL −1 gallic acid in a mango peel suspension presented anti‐proliferative activity against human colon adenocarcinoma cells LS180. They attributed this effect to the hydrophilic nature, AOX (single electron transfer mechanism) and its high capacity of cellular absorption (75%).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Velderrain‐Rodríguez et al . () demonstrated that 45.7 μg mL −1 gallic acid in a mango peel suspension presented anti‐proliferative activity against human colon adenocarcinoma cells LS180. They attributed this effect to the hydrophilic nature, AOX (single electron transfer mechanism) and its high capacity of cellular absorption (75%).…”
Section: Resultsmentioning
confidence: 99%
“…The structural feature, responsible for the antioxidative and free-radical scavenging activity of gallic acid consists of three adjacent hydroxyl groups. The antioxidant activity of gallic acid is based on a single-electron transfer mechanism [33]. In the raw samples, higher TOC values compared with the control were associated with seven treatments.…”
Section: Fatty Acid Oxidationmentioning
confidence: 99%
“…The carousel was put into the extraction equipment, and a 10-min extraction program was started. The variables that had been selected to be optimized were the extraction solvent (25-75% MeOH in water), the extraction temperature (50-100 • C), the extraction solvent pH (2)(3)(4)(5)(6)(7), and the sample mass (g): solvent volume (mL) ratio (0.5:10-0.5 :20).…”
Section: Microwave-assisted Extractionmentioning
confidence: 99%
“…Nowadays, the use of vegetables and fruits in the treatment and prevention of different chronic diseases, like cancer, based on their interesting antioxidant or anti-inflammatory properties, is increasing [1][2][3][4][5]. Euterpe is a genus of tropical palm trees native to Northern South America that produces three predominant fruits: Euterpe edulis Mart., Euterpe precatoria Mart., and Euterpe oleracea Mart.…”
Section: Introductionmentioning
confidence: 99%